ANALISIS MORFOLOGI DAN GEOLOGI BENCANA TANAH LONGSOR DI DESA LEDOKSARI KABUPATEN KARANGANYAR - Prawiradisastra, Suryana (Badan Pengkajian dan Penerapan Teknologi, 2008)
Karanganyar administratively belongs to Central Java Province, the average height is 511 meters on the sea surface and the climate is tropic with temperature 22º - 31º. The area of Karanganyar district is 77,378.6374 ha, which consists of the rice field 22,844.2597 ha and the dry ground is 54,534.3777 ha. Based on data from six weather forecast offices located in Karanganyar, the number of rain day during 2005 year were 99 days with the average of rainfall 6,017 mm, where the highestrainfall happened in March and the lowest happened in July and in August. The northern part occupied by the Lawu volcano is a part of the active Quarternary volcanic zone. Hills north of Tirtomoyo river, are a folding hills showing a NE-SW direction. Morphogenetically, the mountainous terrain in this area is influenced by structure and lithologic characteristics.